Nurse performing handover using the SBAR method at the Guido Valadares National Hospital, Timor-Leste - Maria Fransiska Eflin; Eulalia Marcia de Lima Amaral (Health Gate, 2026)
Background; nstructured handover is a major cause of clinical miscommunication and patient safety incidents in the emergency department. The SBAR (Situation, Background, Assessment, Recommendation) method is recommended as a standard for patient safety-based communication, but its implementation in hospitals in developing countries is still limited. Objective: To describe the improvement in nurses' performance in handovers using the SBAR method. Methods: This study used a descriptive design that describes changes in nurses' knowledge and skills after handovers using the SBAR method were implemented in the ward. A sample of 20 nurses was taken from the entire population of nurses in the Internal Medicine Unit at Guido Valadares National Hospital in Dili. Knowledge and skills data were collected before and after implementation using a questionnaire and checklist. Results: Average knowledge increased from 56.4 to 84.7 (+50.2%). The proportion of nurses performing structured handovers increased from 30% to 85%. The implementation of SBAR improved communication clarity, accelerated clinical decision-making, and improved continuity of care. Conclusion: The implementation of the SBAR method of handover can be continued to improve effective communication which will have an impact on improving the quality of nursing services.